Qulaity of Life in Cystic Fibrosis Children - Kianifar, Hamid-Reza (Tehran University of Medical Sciences, 2013)
OBJECTIVE: Cystic fibrosis (CF) is a chronic, multisystem genetic disease with a wide variability in clinical severity. The measurement of quality of life in CF provides additional information about the impact of this disease. This article tries to assess quality of life (QoL) in children and adolescents with CF and to compare it with control group. METHODS: Patients 2-18 years old with admission diagnosis of cystic fibrosis entered the study. QoL was observed in CF patients and compared with control group. FINDINGS: Based on children's reports, significant differences between the CF patients and control group were noted for emotional, physical, social, school performance, and total scores (P<0.05). Based on parents’ reports, quality of life score in CF patients from the physical point of view as well as social and total scores were decreased (P<0.05). CONCLUSION: QoL in CF patients seems to be low, and therapy programs should take into account the suggestive perceived quality of life.